2010
DOI: 10.1111/j.1471-0528.2010.02752.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of rapid tests and other existing strategies for screening and management of early‐onset group B streptococcus during labour

Abstract: Objective To determine the cost-effectiveness of alternative screening and prevention strategies, including rapid intrapartum testing, for prevention of early-onset neonatal group B streptococcus (GBS) infection in the UK. Design A decision model was developed to investigate the costeffectiveness of screening and prevention strategies for GBS. A strategy of doing nothing was also considered. Deterministic and probabilistic sensitivity analyses were carried out.Setting Two large UK based obstetric units.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
1
14
0
4
Order By: Relevance
“…33 Kaambwa et al tried to determine the cost-effectiveness of alternative screening and prevention strategies, including rapid intrapartum testing, for the prevention of early-onset neonatal GBS infection in the UK. 34 The authors found that the most cost-effective strategy was the provision of routine intrapartum antibiotic prophylaxis to all women without prior screening, but they also agreed that this was unlikely to be acceptable, given the broader concerns related to antibiotic use. 34 A 2009 Cochrane review critiqued the effectiveness of intrapartum antibiotic prophylaxis to reduce early-onset neonatal GBS infection.…”
Section: Discussionmentioning
confidence: 97%
“…33 Kaambwa et al tried to determine the cost-effectiveness of alternative screening and prevention strategies, including rapid intrapartum testing, for the prevention of early-onset neonatal GBS infection in the UK. 34 The authors found that the most cost-effective strategy was the provision of routine intrapartum antibiotic prophylaxis to all women without prior screening, but they also agreed that this was unlikely to be acceptable, given the broader concerns related to antibiotic use. 34 A 2009 Cochrane review critiqued the effectiveness of intrapartum antibiotic prophylaxis to reduce early-onset neonatal GBS infection.…”
Section: Discussionmentioning
confidence: 97%
“…However, because of the reimbursement system used in most countries (diagnostic related groups), hospitals are not inclined to add laboratory examinations to in-hospital treatments, and it is difficult to convince hospital administrators to invest in strategies to spare antibiotic use if their application is more costly than the price of the antibiotic itself. Indeed, as shown by Kaambwa [37], the most costeffective method for the prevention of GBS neonatal sepsis is ''treat all'' (routine untargeted IAP to all). However, this attitude leads to unneeded antibiotic treatment for many pregnant mothers, with associated side effects for the mother and child.…”
Section: Point Of Care Detection Nucleic-acid Based Assays For Screenmentioning
confidence: 99%
“…However, this attitude leads to unneeded antibiotic treatment for many pregnant mothers, with associated side effects for the mother and child. For the moment, the second best approach in terms of cost effectiveness is to base IAP on antenatal cultures [37]. This is, however, likely to change in the next few years.…”
Section: Point Of Care Detection Nucleic-acid Based Assays For Screenmentioning
confidence: 99%
“…Further studies using real-time PCR performed in intrapartum setting were needed to identify targeted population and settings where the test will be most useful. In these last years, studies not supporting the intrapartum PCR screening as a cost-effective strategy in comparison with culture screening at around 35-37 weeks of gestation, used data from older less accurate PCR equipment [32,113].…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 99%